Change in Leaf Morphology in the Experimentally Synthesised Autotetraploids of Sandalwood - Kapoor, M. L.; Kedharnath, S. (Indian Forester, 1976)
EsperimentalJy synthesised autotetraploids in Sandalwood appeared very distinct from their corresponding diploids because of a marked change brought about in the morphology of the leaves and the angle in which they are held on the branches. To quantify these differences measurements were recorded on length width and thickness of leaf, length, thickness and angle of petiole. frequency and size of stomata. Length of leaf and petiole and frequency of stomata. per unit area showed a decrease in the tetraploids whereas for width and thickness of leaf, thickness of petiole and length and width of stomata the tetraploids showed an increase over the measurements for the diploids.